Construction and practice of nursing experimental teaching demonstration centers from university of Traditional Chinese Medicine (中医药院校护理实验教学示范中心建设与实践) - YAO Qiuli (姚秋丽); Wang Chao (王超); LI Weihong (李卫红); WEN Xiaojing (温晓静); YUE Shujin (岳树锦) (Journal of International Translational Medicine Limited, 2022)
This paper summarized the construction objectives, construction ideas, construction measures and construction results of the experimental nursing center of Beijing University of Chinese Medicine, and reviewed the practical experience of the construction of the center, so as to provide reference for the development of nursing laboratory construction in other colleges and universities. (通过对北京中医药大学护理实验中心的建设目标、建设思路、建设举措与成效等方面进行梳理, 总结中心建设实践经验, 以期为兄弟院校护理实验室建设提供参考。)